RF power amplifiers - Kazimierczuk, Marian K. (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2015)
This second edition of the highly acclaimed RF Power Amplifiers has been thoroughly revised and expanded to reflect the latest challenges associated with power transmitters used in communications systems. With more rigorous treatment of many concepts, the new edition includes a unique combination of class-tested analysis and industry-proven design techniques. Radio frequency (RF) power amplifiers are the fundamental building blocks used in a vast variety of wireless communication circuits, radio and TV broadcasting transmitters, radars, wireless energy transfer, and industrial processes. Through a combination of theory and practice, RF Power Amplifiers, Second Edition provides a solid understanding of the key concepts, the principle of operation, synthesis, analysis, and design of RF power amplifiers. This extensive update boasts: up to date end of chapter summaries; review questions and problems; an expansion on key concepts; new examples related to real-world applications illustrating key concepts and brand new chapters covering'hot topics' such as RF LC oscillators and dynamic power supplies. Carefully edited for superior readability, this work remains an essential reference for research & development staff and design engineers. Senior level undergraduate and graduate electrical engineering students will also find it an invaluable resource with its practical examples & summaries, review questions and end of chapter problems. Key features: A fully revised solutions manual is now hosted on a companion website alongside new simulations. Extended treatment of a broad range of topologies of RF power amplifiers. In-depth treatment of state-of-the art of modern transmitters and a new chapter on oscillators. Includes problem-solving methodology, step-by-step derivations and closed-form design equations with illustrations.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Power amplifiers; Amplifiers, Radio frequency; Electric resonators; TECHNOLOGY & ENGINEERING -- Mechanical; Amplifiers, Radio frequency; Electric resonators; Power amplifiers; Electronic books; Electronic books